Renate Bertlmann : works 1969-2016 : ein subversives Politprogramm - Bertlmann, Renate; Schor, Gabriele; Morgan, Jessica (2016)
"Renate Bertlmann is among the most significant artists of the 1970s Feminist Avant-garde. Born in 1943, she lives and works in Vienna. Here, the SAMMLUNG VERBUND, Vienna presents the first comprehensive monograph of her work. The book, created in close collaboration with the artist, is published in both German and English and contains 300 illustrations from a career spanning more than five decades. Bertlmann divides her work into Pornography, Irony and Utopia, with all three areas gathered under the motto AMO EROG SUM (I love, therefore I am). Her work artfully stages the encounter of opposites: female and male, soft and hard, attraction and repulsion, eroticism and asceticism. The essays in the book provide an art historical overview of the motif of the bride, interpret Bertlmann's work in the light of Freudian and Lacanian psychoanalysis, explore themes of skin and touch, and contextualize her work within the broader history of feminism. The volume also contains an extensive interview with the artist, a biographical overview, and an illustrated chronology of her films, performances, and staged photographs"--
Introductory Remarks on the Works of Renate Bertlmann / Gabriele Schor -- Obsession, Protest, Spiritualilty. Interview with Renate Bertlmann / Gabriele Schor -- After Freud: Members Only / Jessica Morgan -- Laughter in Utopia. The Janus Faces of Renate Bertlmann's Art / Katharina Sykora -- The Subversive Bride. A Cultural- and Art-Historical Overview / Berthold Ecker -- Laughing at the Law: Renate Bertlmann's Theater of the Phallus / Abigail Solomon-Godeau.
Published to accompany the exhibition "Amo ergo sum : ein subversives Politprogramm" = A subversive political program, Sammlung Verbund, Vienna, 25th February-30 June 2016.
Includes bibliographical references.
Text in German and English.
Keywords: Bertlmann, Renate, -- Exhibitions; 1900-2099; Art, Austrian -- 20th century -- Exhibitions; Art, Austrian -- 21st century -- Exhibitions; Feminism and art -- Exhibitions